Who Shall Have the Orphanage? Maria Theresa´s Foundation for the Establishment of Debrecen Orphanage and a Century of Controversies concerning Its Confessional Character - Kušniráková, Ingrid (Church History Review, 2025)
In 1760, the town of Debrecen loaned 30,000 florins to the Royal Treasury to cover the expenses related to the war against Prussia. Fourteen years later, the town decided to consider this loan a gift to Maria Theresa. However, a generous gift turned against the city itself when the empress decided to use the means for the foundation of the Catholic orphanage in a strikingly Calvinist town. Taking into consideration the Calvinist majority in the population, she did not define the institution´s confessional objectives clearly, which resulted in endless conflicts in terms of the religious belief of its foster children. On one hand, there was a municipal authority maintaining that Maria Theresa intended to take care of all local orphans regardless of their confession. On the other hand, the Catholic Bishopric of Oradea and the Lieutenancy Council defended a Catholic character of this institution. The dispute was to be resolved by the court in Vienna; however, due to the religious and political situation in the Kingdom of Hungary, the court was postponing the ruling for decades. Ambiguous wording of the foundation charter and the hesitant approach of the Viennese court caused the foundation to commence its activities only 85 years after it had been established. The study examines the course of the dispute over the establishment and confessional definition of the orphanage in Debrecen in the context of the development of religious relations and institutional care for orphaned children in the Kingdom of Hungary.